Bordetella adenylate cyclase toxin is a unique ligand of the integrin complement receptor 3 - Osicka, Radim; Osickova, Adriana; Hasan, Shakir; Bumba, Ladislav; Cerny, Jiri; Sebo, Peter (eLife, 2015)
Integrins are heterodimeric cell surface adhesion and signaling receptors that are essential for metazoan existence. Some integrins contain an I-domain that is a major ligand binding site. The ligands preferentially engage the active forms of the integrins and trigger signaling cascades that alter numerous cell functions. Here we found that the adenylate cyclase toxin (CyaA), a key virulence factor of the whooping cough agent Bordetella pertussis, preferentially binds an inactive form of the integrin complement receptor 3 (CR3), using a site outside of its I-domain. CyaA binding did not trigger downstream signaling of CR3 in human monocytes and CyaA-catalyzed elevation of cAMP effectively blocked CR3 signaling initiated by a natural ligand. This unprecedented type of integrin-ligand interaction distinguishes CyaA from all other known ligands of the I-domain-containing integrins and provides a mechanistic insight into the previously observed central role of CyaA in the pathogenesis of B. pertussis.
Keywords: Animals; křečci praví; makrofágový antigen 1; buněčné linie; adenylate cyclase toxin; vazba proteinů; Adenylate Cyclase Toxin; Bordetella pertussis; lidé; complement receptor 3; infectious disease; Cell Line; cAMP signaling; biochemistry; Macrophage-1 Antigen; interakce hostitele a patogenu; E. coli; zvířata; Host-Pathogen Interactions; microbiology; Protein Binding; adenylátcyklasový toxin; Cricetinae; Humans